Pendampingan Pembelajaran Matriks Berbantuan Papan Determinan dan Ludo Matematika di MAS Madani Alauddin Pao-Pao - Nurul Fajri Ninsih; Sahratul Jannah; Sri Sulasteri; Sriyanti, A. (KHIDMAH: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aimed to strengthen students’ understanding of matrix multiplication, matrix determinants, and determinant properties through learning assistance supported by a determinant board, student worksheets, discovery learning, and a mathematics ludo game. The activity involved 29 students of Grade XI MIPA 4 at MAS Madani Alauddin Pao-Pao during the 2023/2024 academic year and was conducted in four 80-minute meetings. The activity evaluation operationally adopted a one-group pretest-posttest pre-experimental design. The initial test consisted of five questions with a maximum score of 100, while the final evaluation was administered individually through a mathematics ludo game. Data were analyzed descriptively by calculating mean scores, score ranges, score gains, and mastery percentages using 75 as the mastery criterion. The mean score increased from 53.45 to 85.34, representing a gain of 31.90 points (59.68%). The number of students achieving a score of at least 75 increased from 5 students (17.24%) to 27 students (93.10%). The improvement was associated with reinforcement of integer operations as prerequisite knowledge, visual media that guided determinant procedures, collaborative worksheet-based practice, and game-based evaluation that supported student engagement. These results should be interpreted cautiously because the initial and final assessments were not fully identical, and no comparison group was used. Stepwise assistance supported by concrete media and educational games may serve as a practical alternative for strengthening matrix understanding in Islamic senior secondary schools.